2010
DOI: 10.1345/aph.1m365
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Treatment for Insomnia in Pediatric Patients with Attention-Deficit/Hyperactivity Disorder

Abstract: Available data suggest that melatonin is a well-tolerated and efficacious treatment option for pediatric patients with chronic SOI and ADHD. Regulated melatonin products and larger, well-designed trials to establish optimal dosing regimens and long-term safety are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 23 publications
0
50
0
2
Order By: Relevance
“…The therapeutic use of exogenous melatonin (5 mg melatonin in the evening), used to reset the timing function of the SCN, is associated with advanced sleep onset and DLMO compared to placebo in children with idiopathic chronic sleep-onset insomnia (Smits et al, 2001;Smits et al, 2003). Also in children with ADHD, melatonin administration is considered to be an effective treatment of initial SOI (Bendz and Scates, 2010). Significant improvement in sleep parameters such as sleep onset and sleep onset latency were described in both non-stimulant treated (Hoebert et al, 2009;Van Der Heijden et al, 2007) and stimulant treated (Tjon Pian Gi et al, 2003;Weiss et al, 2006) children with ADHD and insomnia.…”
Section: Melatoninmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic use of exogenous melatonin (5 mg melatonin in the evening), used to reset the timing function of the SCN, is associated with advanced sleep onset and DLMO compared to placebo in children with idiopathic chronic sleep-onset insomnia (Smits et al, 2001;Smits et al, 2003). Also in children with ADHD, melatonin administration is considered to be an effective treatment of initial SOI (Bendz and Scates, 2010). Significant improvement in sleep parameters such as sleep onset and sleep onset latency were described in both non-stimulant treated (Hoebert et al, 2009;Van Der Heijden et al, 2007) and stimulant treated (Tjon Pian Gi et al, 2003;Weiss et al, 2006) children with ADHD and insomnia.…”
Section: Melatoninmentioning
confidence: 99%
“…Although light therapy seems effective in adults with ADHD and a delayed sleep phase (Rybak et al, 2004), so far, no melatonin medication studies in this population are available. Well-designed studies to establish optimal dosing regimens for different age groups and long-term safety are needed (Bendz and Scates, 2010).…”
Section: Circadian Profiles In Adhd 26mentioning
confidence: 99%
“…[18,19,32,33] Dikkat eksikliği/hiperaktivite ve uyku başlangıcında bozukluğu (sleep-onset insomnia) olan çocuk hastalar için melatonin tedavisi öne-rilmektedir. [34] Ancak bazı araştırmalarda uyku problemi yaşayan erişkin kişilerdeki melatonin düzeyinin uyku problemi olmayan kişilerden düşük olmadığı bulunmuştur. [35] Bazil ve arkadaşları dirençli epileptik hastalarda düşük melatonin düzeyleri saptamışlardır.…”
Section: Melatonin Uyku Ve Uykusuzlukunclassified
“…Parents reported that the melatonin improved their children's daytime behavior (Hoebert et al, 2009). A literature review confirmed that children with ADHD and insomnia showed improvement in regards to sleep onset latency when taking melatonin (Bendz & Scates, 2010). However, these results are limited as there are few studies, and most of them have small sample sizes.…”
Section: Medications For Sleep Problems In Children With Adhdmentioning
confidence: 99%